HUBUNGAN KONSUMSI KOPI DAN KEBIASAAN MEROKOK TERHADAP PENINGKATAN TEKANAN DARAH PADA NELAYAN DI DESA WARULOR PACIRAN LAMONGAN - Fithri Fifianah; Detti Nur Irawati; Nenny Triastuti; M. Perdana Airlangga (PROCEEDING UMSURABAYA, 2023)
Abnormalities of blood pressure are divided into two kinds, namely as increased blood pressure or high blood pressure (hypertension) and low blood pressure (hypotension). Hypertension or commonly known as high blood pressure is a chronic medical condition in which the blood pressure in the arteries increases, requiring the heart to work harder to circulate blood through the blood vessels throughout the body. Hypertension is also called the "Silent Killer" where sufferers of hypertension do not realize or feel the symptoms of this disease. There are various risk factors that can influence the occurrence of hypertension in a person, including gender, age, and a person's lifestyle.  Knowing the relationship between coffee consumption and smoking habits on increasing blood pressure in fishermen in the village of Warulor Paciran Lamongan.  The type of research used in this study is an observational analytic method with a cross sectional approach. The sample size in this study was calculated using the slovin formula and the results obtained were that the required respondents were 75 respondents. Non-probability sampling technique with purposive sampling type. The research sample used was fishermen in Warulor Village who smoked and drank coffee and were willing to be respondents by filling out informed consent and exclusion criteria, namely fishermen who had a history of certain diseases such as heart disease, diabetes mellitus, and kidney failure. In addition, fishermen who did not consume coffee and have no smoking habit for more than 1 month. Of the 75 research respondents who were fishermen, all were male. The most recorded age profile was over 50 years old with a total of 27 people (36%) of the total sample used. Meanwhile, the number of fishermen who were less than 20 years old was 4 people (5.3%). The description of the coffee consumption of the fishermen of Warulor Paciran Lamongan who became the research sample was that most fishermen consumed 1-2 cups of coffee/day at most 60 people (80%). The Chi-Square value from the crosstabs analysis is 0.130 with a p-value of 0.718 which is greater than the error rate of 0.05. These results conclude that there is no significant association between coffee consumption and increased blood pressure. Based on the results of the calculation of the Brinkman index, it can be seen that smoking habits among fishermen are in the light category, namely 41 people (54.7%), in the moderate category, there are 22 people (29.3%) and 12 people (16%), including the heavy category. The Chi-Square value from the crosstabs analysis resulted in 19.939 with a p-value of 0.000 which is smaller than the error rate of 0.05. These results conclude that there is a significant association between smoking habits and increased blood pressure. There is no relationship between coffee consumption and increased blood pressure and there is a relationship between smoking habits and increased blood pressure among fishermen in Warulor Paciran Lamongan Village.Keywords         : Increased blood pressure, Coffee, Cigarettes, Fishermen